THE USING OF TWO STAY TWO STRAY (TSTS) STRATEGY ON STUDENTS’ READING COMPREHENSION - Mardin Silalahi; Yuni Winda Sary (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2020)
The objective of this research was to find out the effect of using Two Stay Two Stray (TSTS) strategy on students’ reading comprehension at the tenth grade of SMA Negeri 4 Pematangsiantar. In this research, the researcher used a quantitative research and the method of this research is experimental research by used true-experimental research design. The population of this research was the students of the tenth grade PMIA SMA Negeri 4 Pematangsiantar, there are seven classes and the total of population in this research was 249 students. To determine the sample, the researcher make a lottery, the sample of this research were two classes. The first class is taken from X PMIA-6 with 36 students as control class and the second class is taken from X PMIA-7 with 36 students as experimental class. So, the total of the sample in this research is 72 students. In analyzing the data, the researcher used SPSS version 2.1. The result of this research was the students’ score pre-test in control class are 1876 with the mean score 52.11 and the students’ score post-test in control class are 2152 with the mean score 59.78. Before the treatment of Two Stay Two Stray strategy, the students’ prior knowledge in reading comprehension was less with score pre-test are 1870 with the mean score 51.94. After the treatment using Two Stay Two Stray strategy, the students’ score post-test in reading comprehension had been improved are 2808 with the mean score 78.00. It means that the scores of experimental class are higher than in control class because the researcher conducted the research in experimental class by using a treatment (Two Stay Two Stray Strategy). Then the results of hypothesis testing using T-Test obtained tcount (9.86) >ttable (1.66), it can be concluded that Ho is rejected and Ha is accepted. It means that the using of Two Stay Two Stray strategy affects significantly on students’ reading comprehension at the tenth grade of SMA Negeri 4 Pematangsiantar